Achieving good-quality consent: review of literature, case law and guidance. Issue 5 (31st May 2020) - Normahani, P; Sounderajah, V; Harrop-Griffiths, W; Chukwuemeka, A; Peters, N S; Standfield, N J; Collins, M; Jaffer, U
Abstract: Background: Informed consent is an integral part of clinical practice. There is widespread agreement amongst health professionals that obtaining procedural consent needs to move away from a unidirectional transfer of information to a process of supporting patients in making informed, self-determined decisions. This review aimed to identify processes and measures that warrant consideration when engaging in consent-based discussions with competent patients undergoing elective procedures. Methods: Formal written guidance from the General Medical Council and Royal College of Surgeons of England, in addition to peer-reviewed literature and case law, was considered in the formulation of this review. Results: A framework for obtaining consent is presented that is informed by the key tenets of shared decision-making (SDM), a model that advocates the contribution of both the clinician and patient to the decision-making process through emphasis on patient participation, analysis of empirical evidence, and effective information exchange. Moreover, areas of contention are highlighted in which further guidance and research are necessary for improved enhancement of the consent process. Conclusion: This SDM-centric framework provides structure, detail and suggestions for achieving meaningful consent. Graphical Abstract: This review aimed to identify processes and measures that warrant consideration when engaging in consent-based discussions with competent patients undergoing elective procedures. A strategy for shared decision-making